The diagnostic utility of abdominal ultrasound in adult patients presenting with non-traumatic abdominal pain to the emergency centre of Khayelitsha Hospital - Dausab, Gaudencia Florence (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMed)--Stellenbosch University, 2022.